Responses of adult spotted lanternflies to artificial aggregations composed of all males or females - Cooperband, Miriam F.; Murman, Kelly (Frontiers in Insect Science, 2022)
Spotted lanternflies (SLF) Lycorma delicatula are economically important invasive planthoppers discovered in North America in 2014. SLF are gregarious, but how they locate each other, or who finds whom and when, is poorly understood. Here we describe adult SLF behavior and phenology on their preferred host, Ailanthus altissima, under field conditions, in the context of both aggregation and mate-location, since SLF demonstrated aggregation prior to mating. We documented aggregation behavior of adults and found we could manipulate free-living SLF populations in both number and sex ratio by the placement of confined populations of SLF males or females on trees. Trap capture of arriving SLF was significantly higher on trees with confined SLF aggregations than on control trees, and was corroborated with photographic data, demonstrating the manipulation of attraction and aggregation behavior. Sex ratios of trapped SLF arrivals were significantly more male-biased on trees with confined males and more female-biased on trees with confined females, evidence that the male- and female-biased sex ratios observed on trees naturally can be explained by sex-specific conspecific signals. SLF sex ratios shifted over time in the same pattern over two consecutive years. A mark-release-recapture study over time found that 1) SLF behavior is density dependent and strongly influenced by natural populations, 2) released females were captured significantly more on trees with caged females, particularly prior to mating, and 3) released males were captured significantly more on trees with caged females starting at mating time. Photographic data revealed that most clustering behavior (a measure of courtship) of free-living SLF began on trees with caged females during mating time, but not on trees with caged males or controls. We describe adult male and female SLF phenology whereby 1) aggregation behavior occurs, 2) males and females arrive at different times, 3) females began to aggregate several weeks prior to mating, 4) males subsequently joined aggregations at the time of mating, and 5) aggregation continued into oviposition. Population density and aggregation behavior were found to be key factors in their natural history which can be manipulated, providing a foothold for future research. Possible mechanisms for future exploration are discussed.